DRAGON LAND - Reynolds, Maureen, 1938- (Edinburgh : Black & White Publishing, 2014)
Lizzie Flint learns things a young girl shouldn't know. During WWII, she learns that her father is missing in action, and she and her mother will have to live with her grandmother until he is found. Grown up, Lizzie develops an adventurous streak and travels to Hong Kong to take up a teaching post. She marries, but her husband is sent to Shanghai to report on the Japanese bombings - and Lizzie fears that, like her father, she will never see her husband again.
Keywords: British -- China -- Fiction; Sino-Japanese War, 1937-1945 -- Fiction; China -- History -- 20th century -- Fiction; Domestic fiction; Historical fiction